Safe procedure development to manage hazardous drugs in the workplace - Marisa Gaspar Carreño; Rubén Achau Muñoz; Fátima Torrico Martín; Juan José Agún Gonzalez; Jose Cristobal Sanchez Santos; Ana Cristina Cercos Lletí; Pedro Ramos Orozco (Elsevier, 2017)
Objective: To develop a safety working procedure for the employees in the Intermutual Hospital de Levante (HIL) in those areas of activity that deal with the handling of hazardous drugs (MP). Methods: The procedure was developed in six phases: 1) hazard definition; 2) definition and identification of processes and development of general correct work practices about hazardous drugs' selection and special handling; 3) detection, selection and set of specific recommendations to handle with hazardous drugs during the processes of preparation and administration included in the hospital GFT; 4) categorization of risk during the preparation/administration and development of an identification system; 5) information and training of professionals; 6) implementation of the identification measures and prevention guidelines. Results: Six processes were detected handling HD. During those processes, thirty HD were identified included in the hospital GFT and a safer alternative was found for 6 of them. The HD were classified into 4 risk categories based on those measures to be taken during the preparation and administration of each of them. Conclusions: The development and implementation of specific safety-work processes dealing with medication handling, allows hospital managers to accomplish effectively with their legal obligations about the area of prevention and provides healthcare professional staff with the adequate techniques and safety equipment to avoid possible dangers and risks of some drugs.